2023
DOI: 10.21037/acs-2023-avs1-20
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of aortic root aneurysms

Bulat A. Ziganshin,
Nicole Kargin,
Mohammad A. Zafar
et al.

Abstract: The aortic root has a different embryologic origin from all other segments of the human aorta, a feature that likely confers unique susceptibilities, anatomical patterns, and clinical behavior of aneurysm disease in this vital location. In this manuscript, we review the natural history of ascending aortic aneurysm, with a specific focus on the aortic root. The specific central message is that root dilatation is more malignant than ascending dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Genetically mediated aortic root aneurysms typically exhibit a more aggressive natural history than other ascending aortic aneurysms that do not involve the root. A study from the Yale Aortic Institute demonstrated an increased risk of rupture and dissection for aortic root aneurysms surpassing 5 cm, with mid-ascending aorta risks intensifying beyond 5.25 cm to 5.5 cm [ 6 ]. Recent guidelines from the American Heart Association and American College of Cardiology recommend resection timings based on these measurements [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically mediated aortic root aneurysms typically exhibit a more aggressive natural history than other ascending aortic aneurysms that do not involve the root. A study from the Yale Aortic Institute demonstrated an increased risk of rupture and dissection for aortic root aneurysms surpassing 5 cm, with mid-ascending aorta risks intensifying beyond 5.25 cm to 5.5 cm [ 6 ]. Recent guidelines from the American Heart Association and American College of Cardiology recommend resection timings based on these measurements [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing is favorable because it can predict the natural course of malignant aortic disease. More than 70 genes, including FLNA, are implicated in thoracic aortic disease, and mutation of each particular gene can modify their "typical" natural history, which can affect counseling for prophylactic surgery [ 6 ], and if the pathogenic variant is identified on genetic testing, cascade testing for at-risk relatives with thoracic aortic imaging and further gene-based management is recommended [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the aneurysm reached a diameter of 95 mm with the involvement of all three coronary sinuses, indicative of its rareness in this clinical presentation. Although symptomless SVOA often remains asymptomatic, large ones can interfere with cardiac valve action and compression effects, possibly leading to sinus rupture due to increased intraluminal pressure and thinning of the wall, with bleeding into neighboring chambers 2 . Studies suggest that SOVA is often associated with significant morbidity and mortality and timely intervention is necessary 3 …”
Section: Introductionmentioning
confidence: 99%
“…Although symptomless SVOA often remains asymptomatic, large ones can interfere with cardiac valve action and compression effects, possibly leading to sinus rupture due to increased intraluminal pressure and thinning of the wall, with bleeding into neighboring chambers. 2 Studies suggest that SOVA is often associated with significant morbidity and mortality and timely intervention is necessary. 3 Computerized tomography angiography provides comprehensive views of the lesion position from various angles and allows clear visualization of the aneurysm's three-dimensional form, while TEE aids in detecting any thrombus formation, surrounding anatomy, and coexisting ventricular septal defect and aortic valve abnormality.…”
mentioning
confidence: 99%
“…Aortic root aneurysms pose a significant clinical challenge, often necessitating surgical intervention to mitigate the risk of catastrophic events [1,2]. While the conventional full sternotomy approach has long been the preferred method for aortic aneurysm repair, recent advancements have seen the emergence of valve-sparing techniques as endorsed by current guidelines, particularly when addressing aortic regurgitation resulting from aneurysmal widening of the aorta [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%